Transparansi Laporan Keuangan dan Efektivitas Pengendalian Internal: Dimoderasi Kepemimpinan Spiritual OPD Bengkulu - Putra, Rindi Exi; Aziza, Nurna (Penerbit Goodwood, 2025)
Purpose: This study examines the effect of financial statement transparency on internal control effectiveness, with mental leadership as a moderating variable in Local Government Organizations (OPD) in Bengkulu City. Methodology/approach: This study employed a quantitative approach using a survey method distributed to three respondents from each local government organization (OPD), resulting in a total of 90 respondents from 30 OPDs. Results: The results show that financial reporting transparency positively influences internal control effectiveness, while spiritual leadership strengthens this effect by fostering ethical values and accountability, highlighting the importance of value-based leadership in public sector financial control systems. Conclusion: Financial reporting transparency enhances internal control effectiveness, and spiritual leadership strengthens this relationship by fostering ethical values and accountability, thereby creating a more effective and accountable public sector governance system. Limitations: The limited geographical scope of one city may restrict the generalization of the research findings. Additionally, due to the limited quantitative approach and the number of variables analyzed, it is not possible to fully understand the complexity of the factors influencing the effectiveness of internal control in the public sector. Contribution: This study makes a theoretical contribution by expanding the discourse on the impact of spiritual values on public sector financial management leadership while simultaneously enhancing the application of agency theory and management. In practice, the results provide valuable insights for local governments in designing strategies to improve financial transparency and accountability through a value-oriented management approach.